Ciberseguridad y Derechos Humanos: respuestas estatales e individuales a las revelaciones de espionaje de Snowden (Coyuntura) - Crespo-Pazmiño, Daniel (2019)
Four days after the withdrawal of Assange’s asylum, the Ecuadorian government announced that it suffered more than four million cyberattacks. Clearly, the cyberspace is an environment that is not exempt from risks, opportunities, and interests. The political responses of different actors reposition the debate on the role of informants and States in the defense of Internet security on the. Cybersecurity is more than the protection of attacks on critical infrastructures; it also involves the defense of the virtual rights of the people. Through an analysis based on cybersecurity and international political economy, this paper demonstrates the way in which different actors respond to the problem of security and respect for rights.